2017
DOI: 10.18488/journal.aefr/2017.7.1/102.1.27.42
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Women Entrepreneurs Motivation in SMEs: A Quantitative Study in Asia Pacific Countries

Abstract: Contribution/ OriginalityThis paper primary contribution in finding the motivation of Muslim women entrepreneurs in Asian Pacific SMEs and proposes some solutions in elevating their position as businesswomen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 12 publications
10
18
0
2
Order By: Relevance
“…The findings also revealed that the students with entrepreneurial/business experience expressed a higher intention to start own business. This result is consistent with the findings of earlier studies which reported that students with previous business experience have a significant and positive influence on their ambition to pursue an entrepreneurial career [19,20,32,95]. This is an expected finding given that business experiences or activities provide students with an opportunity to promote the kind of creative thinking and idea generation central to innovation and new venture development, to acquire certain business skills, confidence and vision, all of which contribute to inclination to start a new business.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings also revealed that the students with entrepreneurial/business experience expressed a higher intention to start own business. This result is consistent with the findings of earlier studies which reported that students with previous business experience have a significant and positive influence on their ambition to pursue an entrepreneurial career [19,20,32,95]. This is an expected finding given that business experiences or activities provide students with an opportunity to promote the kind of creative thinking and idea generation central to innovation and new venture development, to acquire certain business skills, confidence and vision, all of which contribute to inclination to start a new business.…”
Section: Discussionsupporting
confidence: 93%
“…The logistic regression analyses with the inclusion of all factors as well as correlation analysis between perceptions of career choice and four motives showed that having higher aspiration of acquiring social status, contributing to the national economy, gaining more money/wealth enjoying risk and challenges might be helpful in starting a new business made significant contributions on entrepreneurial intent for Saudi students. This affirms previous studies in finding that females who have higher motivation are more likely to engage in entrepreneurial activities [18,19,[32][33][34][35][36]. Saudi female students perceived themselves as risk and challenge takers and ready to contribute to the national economy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results of the current study reveal that internal factors including self-con dence, risk aversion and need for achievement, and external factors including economic and socio-cultural factors have a positive and signi cant impact on women entrepreneurs' success in Pakistan. So, our ndings support the previous studies results in both of developed and developing economies such as (Azmi, 2017;Rani and Hashim 2017;Muhammad, McElwee, and Dana, 2017) suggested that women entrepreneurs internal behavior self-con dence and motivational force enhance the competitive advantage, these capabilities help them to become a successful women entrepreneur. On the other hand, some other researchers (Muhammad, McElwee, and Dana, 2017;Hasan and Almubarak, 2016) have shown that external factors also in uence women entrepreneurs' success, While, our study is different from developed economies nding because they (Bastian, Sidani, & El Amine, 2018;Laudano, et al, 2018) suggested that these factors cannot signi cantly enhance women entrepreneurs' success.…”
Section: Discussionsupporting
confidence: 90%
“…This research is an attempt to discover factors in uencing the performance of women entrepreneurs in this context. Therefore, past studies scrutinized that family support, self-con dence and motivation (Azmi, 2017), risktaking and motivation (Rani and Hashim 2017), lack of business skills (Muhammad, McElwee, and Dana, 2017) plays a very important role in women employee performance. While, government policies, access to nance, culture and regulation (Muhammad, McElwee, and Dana, 2017) signi cantly affect women-run enterprises' success.…”
Section: Introductionmentioning
confidence: 99%